LAS CABECERAS DE LA PRENSA DIARIA COMO REFUERZO DE LA IDENTIDAD DE MARCA EN LOS PERIÓDICOS DEPORTIVOS ESPAÑOLES IMPRESOS Y - Dra. Belén PUEBLA MARTÍNEZ,Dra. Laura GONZÁLEZ DÍEZ,Dr. Pedro PÉREZ CUADRADO (Fonseca, Journal of Communication, 2023)
Press headers are to daily newspapers the same as brands are to products. Because a newspaper is an object itself which also participates in a double designing process: from information and from product design; and in both cases this serves the same purpose, that the reader feels attracted and comes back for more every day. On that trip, which takes place either to the newsstand or to the computer, to become visible and unique is of paramount importance.